Identification of novel small RNAs in extracellular vesicles produced by Actinobacillus pleuropneumoniae - Giarlã Cunha da Silva; Jéssica Nogueira Rosa; Patrícia Pereira Fontes; Alex Gazolla de Castro; Éverton De Almeida Alves Barbosa; Wellington Ronildo Clarindo; Hilário Cuquetto Mantovani; Yanwen Li; Janine Thérèse Bossé; Paul Richard Langford; Denise Mara Soares Bazzolli (Frontiers in Microbiology, 2023)
Extracellular vesicle (EV) production by bacteria is an important mechanism for microbial communication and host-pathogen interaction. EVs of some bacterial species have been reported to contain nucleic acids. However, the role of small RNAs (sRNAs) packaged in EVs is poorly understood. Here, we report on the RNA cargo of EVs produced by the pig pathogen Actinobacillus pleuropneumoniae, the causal agent of porcine pleuropneumonia, a disease which causes substantial economic losses to the swine industry worldwide. The EVs produced by aerobically and anaerobically grown bacteria were only slightly different in size and distribution. Total cell and outer membrane protein profiles and lipid composition of A. pleuropneumoniae whole cell extracts and EVs were similar, although EVs contained rough lipopolysaccharide compared to the smooth form in whole cells. Approximately 50% of Galleria mellonella larvae died after the injection of EVs. RNAseq, RT-PCR, protection from nuclease degradation, and database searching identified previously described and 13 novel A. pleuropneumoniae sRNAs in EVs, some of which were enriched compared to whole cell content. We conclude that A. pleuropneumoniae EVs contain sRNAs, including those known to be involved in virulence, and some with homologs in other Pasteurellaceae and/or non-Pasteurellaceae. Further work will establish whether the novel sRNAs in A. pleuropneumoniae EVs play any role in pathogenesis.